Vous êtes sur la page 1sur 7

Section 2.

1
Addition of Matrices and
Scalar Multiplication

Notation
 a11 a12 a13 … a1n 
a a22 a23 … a2 n 
 21 
=  a31 a32 a33 … a3n 
A = ( aij )  
 " " " … " 
 am1 am 2 am 3 … amn 

In order to add matrices,


add corresponding entries.

For the operation to be defined,


they must be the same size.

The sum will also be the same size.


If the matrices are not the same size, then the
operation is undefined.
1 2  0 −2 
+
Example: 3 4   3 8 
 
Add corresponding entries
1 + 0 2 − 2 
= 
 3 + 3 4 + 8 
1 0 
= 
 6 12 

1 0  0 2 
 −2 5 + 11 5 
Example:    
 −4 3  1 9 
 1+ 0 0 + 2
=  −2 + 11 5 + 5
 
 −4 + 1 3 + 9 
1 2
=9 10 
 
 −3 12 
 1 −6   0 5 2 
 2 0  +  −1 5 −7 
Example:    
Undefined. Matrices are not the same size.

To multiply a matrix by a scalar,


multiply each entry by the scalar.

 1 −4 −5
2 
Example:  2 3 4 
 2(1) 2( −4) 2( −5) 
=
 2(2) 2(3) 2(4) 
2 −8 −10
=
4 6 8 
 1 0 −2  0 0 1
2  4 1 −1 − 4 1 0 0
Example:    
 −5 0 2  0 2 −3
 2 0 −4   0 0 −4 
 8 2 −2  +  −4 0 0
=   
 −10 0 4   0 −8 12 
 2 0 −8 
= 4 2 −2 
 
 −10 −8 16 

Properties
If A and B are mXn matrices and r & s are scalars:
A+B=B+A Commutative Property of Addition
(A + B) + C = A + (B + C) Associative Property of Addition
(r + s) A = rA + sA Distributive Property
r(A + B) = rA + rB Distributive Property
(rs)A = r(sA) Associative Property of Multiplication
Example: Find A if 3A - 2B = C where
 2 −5  4 3
B=  C= 
1 0  and  −2 1 

So 3 A = C + 2 B
1
and so
A= (C + 2B )
3
1   4 3  2 −5 
  + 2 
= 3   −2 1   1 0 
1   4 3  4 −10 
 + 
= 3   −2 1  2 0  

1  8 −7  
=   
3  0 1  
8 7
3 − 3
= 
0 1 
 3 
Example: If A+B = C
and A - B = D, find A and B if
 2 1  4 −5 
C=  & D= 
 − 3 4   − 1 − 2 

A+B = C
A-B=D
2A = C+D

1
So A= (C + D )
2
1 1   2 1   4 −5  
(C + D ) =    +  
2 2   −3 4   −1 −2  
1  6 −4 
=  
2 − 4 2 
 3 −2 
= 
 − 2 1 
Since A + B = C, then B = C - A
 2 1   3 −2 
C− A=  − 
 − 3 4   − 2 1 
 −1 3
= 
 − 1 3
 3 −2   −1 3
A=   & B= 
 −2 1   − 1 3

Vous aimerez peut-être aussi